TINJAUAN YURIDIS PEMBATALAN PERJANJIAN PENGIKATAN JUAL BELI TANAH DAN BANGUNAN SEBAGAI PERBUATAN MELAWAN HUKUM (Studi Kasus Putusan No. 56/PDT.G.S/2020/PN.BTM) - Sumarni; Megawati Barthos (Fakultas Hukum Universitas Borobudur, 2024)
A sale and purchase agreement is an agreement between a seller and a buyer where the seller is bound to transfer ownership of an item to the buyer and the buyer is bound to pay the price of the item as agreed. In practice, the sale and purchase agreement often does not comply with the provisions that have been previously agreed upon, which can result in violations of the law. This study discusses the application of unlawful acts in the cancellation of the Sale and Purchase Agreement (PPJB) and the legal consequences of the cancellation of the PPJB as in Decision Number 56/Pdt.G.S/2020/PN.Btm. The results of the study indicate that the application of substantive civil law regarding unilateral cancellation of PPJB for land and buildings in Decision Number 56/Pdt.G.S/2020/PN.Btm is in accordance with the concept of unlawful acts. The unilateral cancellation of the PPJB by the defendant is contrary to the principle of fairness and is an unlawful act. In this case, the injured party has the right to receive compensation, as regulated in Article 1365 of the Civil Code, which states that every unlawful act that causes loss to another person requires the responsible party to compensate for the loss.